Post Rift Evolution of the Indian Margin of Southern Africa - (:unkn) unknown (My University, 2016)
The objective of this study is to discuss the evolution of the South African Plateau along the Indian margin ofSouthern Africa. Since the classical works of A. du Toit and L.C. King and the improvement of thermochronologicalmethods and numerical models, the question of the uplift of South African Plateau was highly debatedwith numerous scenarios: early Cretaceous at time of rifting (Van der Beek et al., J.Geophys.Res., 2002), lateCretaceous (Braun et al., Solid Earth, 2014), late Cenozoic (Burke & Gunnell, Geol.Soc.of America, 2008).Limited attention has been paid on the constraints provided by the offshore stratigraphic record of the surroundingmargins. The objective of our study is to integrate onshore and offshore data (seismic profiles andindustrial wells) to (1) analyse the infill of the whole margin (21S to 31S) from its hinterland to the distal deepwater basin, (2) to constrain and quantify the vertical movements. We discuss the impact on accommodation andsediments partitioning, and their significance on South African Plateau uplift history.1. Sedimentary basins of the Indian margin of Southern Africa are related to the break-up of Gondwanaduring late Jurassic, resulting in rifts and flexural basins. First marine incursions started during early Cretaceoustimes (oldest marine outcropping sediments are of Barremian age 128 Ma). The region developed as a normalcontinental shelf at the Aptian-Albian transition (113 Ma).2. The Cretaceous geological history of the basins is characterized by differential uplift and subsidence of thebasement, controlled by structures inherited from break up. As example, major early Cretaceous depocenters of themargin are located on the north of Save-Limpopo uplift (Forster, Paleogography, Paleoclimatology, Paleoecology,1975) showing an eastward drainage pattern, maybe related to a proto Limpopo drainage. Those observationssuggest that the escarpment bordering the Bushveld depression is an old relief inherited fr
Keywords: African Research